2022
DOI: 10.1186/s12894-022-01030-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mini endoscopic combined intrarenal surgery and multitract minimally invasive percutaneous nephrolithotomy specifically for kidney staghorn stones: a single-centre experience

Abstract: Background Staghorn stones require surgical treatment to prevent serious complications. Multitract percutaneous nephrolithotomy (PNL) causes great renal parenchymal injury and blood loss. One-stage endoscopic combined intrarenal surgery (ECIRS) entails the combined use of antegrade nephroscope and retrograde flexible ureteroscope to clear the staghorn stone, which may overcome the limitations of multitract PNL. We aimed to compare the perioperative outcomes of mini ECIRS and multitract minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Liu et al [15] were the only group to make a head-to-head comparison of single-tract PCNL with single-tract ECIRS for stag horn stones, both done in prone position with the latter clearly the winner with a higher one stage SFR (84.4 vs. 57.9%, P = 0.007) and no statistically significant difference in complications. Chen et al [34] compared multitract PCNL vs. single-tract ECIRS in staghorn stones. As ECIRS had equal outcomes with no significant differences for operative time (140 vs. 183 min, P = 0.63) and no differences for haemoglobin loss, blood transfusion, complications or hospital stay they concluded that ECIRS is a safe equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al [15] were the only group to make a head-to-head comparison of single-tract PCNL with single-tract ECIRS for stag horn stones, both done in prone position with the latter clearly the winner with a higher one stage SFR (84.4 vs. 57.9%, P = 0.007) and no statistically significant difference in complications. Chen et al [34] compared multitract PCNL vs. single-tract ECIRS in staghorn stones. As ECIRS had equal outcomes with no significant differences for operative time (140 vs. 183 min, P = 0.63) and no differences for haemoglobin loss, blood transfusion, complications or hospital stay they concluded that ECIRS is a safe equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 162 full-text articles were further evaluated for appropriateness and 127 articles were excluded. Finally, 35 articles were considered eligible and included [1,2 ▪ ,6–13,14 ▪ ,15–17,18 ▪▪ ,19 ▪ ,20–22,23 ▪▪ ,24,25 ▪▪ ,26–36,37 ▪ ,38]. Figure 1 shows the flow diagram of the literature search.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations